An empirical analysis of differences in plagiarism among world cultures. Issue 4 (4th July 2018) - Ison, David C.
ABSTRACT: Academic integrity issues, e.g. plagiarism, continue to plague higher education across the globe. Research has noted that the identification and tolerance of cheating behaviors varies dependent upon local culture. This quantitative, comparative study investigated the potential differences among actual rates of incidence of plagiarism among predominant countries and regions in which the literature identified as having academic integrity problems. This study gathered doctoral dissertations and master's theses from institutions in the selected locations and analyzed them with Turnitin® originality assessment software. Regions and countries evaluated were based on guidance from exigent literature. A Kruskal-Wallis test was conducted to evaluate any differences in the prevalence of plagiarism among these locations. The results indicated that there was a statistically significant difference among groups, χ2 (6, N = 266) = 19.545, p = 0.003, η2 = 0.074. Further analysis determined a mix of findings that both support and deny conceptions in other literature.